2016
DOI: 10.3390/en9110979
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Thermal Behaviors in Window Systems by Monitoring of Surface Condensation Using Full-Scale Measurements and Simulation Tools

Abstract: Abstract:The aim of the present study was to investigate the thermal performance of window systems using full-scale measurements and simulation tools. A chamber was installed on the balcony of an apartment to control the temperatures which can create condensation on the interior surfaces of window systems. The condensation process on the window was carefully scrutinized when outdoor and indoor temperature and indoor relative humidity ranged from −15 • C to −20 • C, 23 • C to 24 • C, and 50% to 65%, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…However, at b > 12 mm, neglecting the convective component can lead to significant errors. For such cases, in the formula for thermal resistance, the authors of [20,21] propose that the convection in the vertical gap between the panes can be taken into account by replacing the value of the gas thermal conductivity by λ eqv :…”
Section: Evaluation Of Heat Transfer Rates Through Window Structuresmentioning
confidence: 99%
“…However, at b > 12 mm, neglecting the convective component can lead to significant errors. For such cases, in the formula for thermal resistance, the authors of [20,21] propose that the convection in the vertical gap between the panes can be taken into account by replacing the value of the gas thermal conductivity by λ eqv :…”
Section: Evaluation Of Heat Transfer Rates Through Window Structuresmentioning
confidence: 99%
“…Windows in apartment buildings have relatively low thermal resistance compared to opaque, insulated building components; thus, condensation easily occurs on their indoor surfaces. For condensation on the indoor surfaces of large windows, there are many adverse effects that can induce secondary damage to floor covering materials (e.g., the generation of mildew) [1][2][3][4][5][6][7][8]. To resolve frequent condensation problems in winter, the Korean government enacted the Design Standard for Preventing Condensation in Apartment Buildings [9], which came into effect in May 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Multistory apartment buildings account for more than 58% of all residential buildings in Korea [6], with most having additional windows on the outdoor side of the balcony to create an unheated indoor space. In many cases, the balcony, which can act as a thermal buffer zone between outdoor and heated indoor spaces, is eliminated to increase the effective floor area indoors (as allowed by law; Figure 1); thus, condensation often occurs on the indoor faces of windows during winter.…”
Section: Introductionmentioning
confidence: 99%
“…Insulating spacers have been introduced to reduce heat loss caused by the thermal bridge in the edge-of-glazing. Previous research has shown that improving spacers could significantly reduce the energy lost through multi-pane windows [11][12][13]. In high-performance windows, such as triple-glazed windows, insulating spacers can reduce window U-value by 12% compared to the U-value with aluminum spacers [11].…”
Section: Introductionmentioning
confidence: 99%
“…Energies 2018, 11, 382 11 of 13 for the edge-of-glazing, corresponding to a temperature difference of approximately 1 • C. As in Case 4, the accuracy of predicting the condensation risk at the edge-of-glazing could be improved most effectively by using the increased local surface thermal resistance at the edges. For example, relative to the measurement of f Rsi at Point E-1, the simulation of Case 2 produces an error of approximately 10%, while the simulation of Case 4 reduces the error to less than 3%, as shown in Table 4.…”
mentioning
confidence: 99%